CONNECTIVISM IN THE REFLECTION OF ICT COMPETENCIES OF TEACHER - KUBRICKÝ, Jan (Trends in education, 2013)
The paper deals with current efforts of integrating the basic principles of connectivism theory to the models of ICT competencies of teacher. The author also discusses the changes that necessitated a different approach in the focus of ICT competencies of teacher as technouser concept, the concept towards the development of the personality of the teacher and the pupil's personality.
Keywords: Connectivism; ICT; Competencies of Teacher